Reinventing Corporate Strategy A Case Study of Malaysia, Airlines - Jain, Kamal K .; Saeed, Mohammad (Gyan Management Journal, 2007)
This paper examines the nature and unique features of airline industry by providing insights into its structure, competitive framework and related elements. Mala_11 sia Airlines has been picked up as a case in point to understand the dimensions of airline industry. The paper examines the corporate strategy of the Malaysia_ Airlines. In this competitive environment where many airlines have not been able· to survive, Malaysia Airlines has been successful in sustaining and growing by constantly reinventing its corporate strategy.